Changes in Ammonium-to-Nitrate Ratio along Faidherbia albida Tree Age Gradients in Arenosols - Solomon Amare; Mitiku Haile; Emiru Birhane (Nitrogen, 2024)
Faidherbia albida can enhance the bio-physicochemical fertility of inherently infertile Arenosols. Changes in the soil ammonium (NH4+)-to-nitrate (NO3−) ratio have agricultural, environmental, and ecological implications. Thus, the present study mainly examined the changes in Arenosol NH4+/NO3− ratios, as influenced by varying Faidherbia albida tree age classes. We collected 40 composite soil samples (4 tree age classes×2 soil depths×5 replications) from 0 to 15 and 15 to 30 cm soil depths following core and auger sampling techniques. Analyses of variance have shown that the highest NH4+/NO3− ratios for soil under the old tree canopies are followed by the medium age. In contrast, the significantly lowest NH4+/NO3− ratios were recorded for soil out-of-canopy. Pearson correlation analysis revealed that the NH4+/NO3− ratio was strongly and positively correlated with clay content, total nematode abundance, the fungi/bacterial biomass ratio, cation exchange capacity, microbial biomass carbon, total nitrogen, and soil organic carbon but negative for sand content, bulk density, and pH. The increment in the plant-available forms of nitrogen might be attributed to the accumulation of biologically fixed nitrogen by the Faidherbia albida tree–Rhizobium bacteria symbiosis. The NH4+/NO3− ratio approached one in soil under the old Faidherbia albida trees. The findings suggest that (1) the ability of soil to retain NH4+ increased and (2) the rate of nitrification might be decreased due to inhibition of nitrification by direct and indirect effects of the tree on the nitrifying group of bacteria. The increment in the NH4+/NO3− ratio could also be due to the lowering of the soil’s pH in the older Faidherbia albida trees because lower pH is known to inhibit the activities of nitrifying bacteria. Moreover, maintaining older Faidherbia albida trees in farmlands could contribute to retaining nitrogen and trigger below- and above-ground communities’ successions and ultimately surpass the productivity of arid and semi-arid Arenosols.